Numerical modelling of flow characteristics over sharp crested triangular hump - Al-Qadami E.H.H.; Abdurrasheed A.S.; Mustaffa Z.; Yusof K.W.; Malek M.A.; Ghani A.A. (Elsevier B.V., 2023)
Computer simulation; Flow of fluids; Numerical models; Rivers; Turbulence models; Weirs; Accurate estimation; Flow over hump; FLOW-3D; Hydraulic parameters; Laboratory experiments; Laboratory measurements; Scientific contributions; Water surface profile; Computational fluid dynamics